Dyrektor szkoły w roli pracodawcy – przegląd wybranych zagadnień funkcjonowania szkoły jako zakładu pracy - Jadach , Katarzyna (Studia Edukacyjne, 2020)
One of the basic tasks that the provisions of the educational law entrust to the headteacher is to be inban employment relationship with the teachers as employees. This role is determined by the status of the educational institution as a workplace, to which the sources of universally and internally binding labor law apply. They impose a number of obligations on the employer, i.e. the headteacher, which should be interpreted in the light of the unique educational, teaching and tutoring tasks implemented within the units of the education system. Principal autonomy is also influenced by the imperative of implication in the educational reality the clause of the child’s good. It is done by application of specific legal provisions, in particular making decisions that create the internal policy of the school staff.